A retrospective analysis of dental implants in patients who received a mandibular overdenture with locator attachment (Annals of Medical Research, 2021)
Aim: The objective of this study is to retrospectively examine the relative superiorities of mandibular overdenture dental implants in terms of diameter, length, age and sex, and to determine the rate of implant survival. Material and Methods: The demographic data showing the age, sex and dental implant distribution by age of 138 patients who underwent dental implant treatment at our clinic between 2011 and 2016 were retrieved from the archival records. Patients who underwent mandibular overdenture with two implant-supported locater attachments were included in the study. The anatomical locations, diameter and length characteristics and rate of loss of the implants were analyzed by way of descriptive statistical analysis.Results: Of 138 patients, 69 were female (50%) and 69 were male (50%), and a total number of 276 dental implants were evaluated. When distribution of these implants was examined, it was found that they were mostly placed in the region of 33-43 (94.2%). The mean age of the patients was 63 with an age range of 40 to 87 years. It was found that the dental implants were applied mostly in patients ranging in age from 60 to 69 years (52.8%). The most common implant diameters were 4 mm (18%), 4.2 mm (18%) and 4.5 mm (17%), respectively. The most common implant lengths were 12 mm (32%) and 14 mm (30%). The rate of implant survival was found to be 97.8%.Conclusion: The mandibular two-implant retained overdenture prosthesis with a locator attachment is a successful treatment method with a high survival rate when factors such as diameter and length of the implant and age and sex of the patient are taken into consideration.
Keywords: Dental implant; overdenture; mandible